PENGARUH RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Mattoasi Mattoasi; Amir Lukum; Nur Hafisah Budi (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
This study aims to determine partially and simultaneously the effect of Return On Equity (ROE) and Earning Per Share (EPS) on stock prices. The research method used is a quantitative research method, where the data used is in the form of secondary data. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019, totaling 30 companies. The number of samples used as many as 20 companies with purposive sampling technique. The data analysis technique used in this research is multiple regression analysis using panel data method. The results of the study partially show that Return On Equity (ROE) has no effect on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019 and Net Profit Margin (NPM) affects stock prices in sub-sector manufacturing companies. sector. food and beverage sector listed on the Indonesia Stock Exchange in 2015-2019. Meanwhile, it simultaneously shows that Return On Equity (ROE) and Earning Per Share (EPS) together have an effect on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019.Keywords: Return On Equity (ROE), Earning Per Share (EPS) and Stock Price